PENGARUH PUASA INTERMITEN DIURAL (PID)TERHADAP MEDIATOR PRO INFLAMASI; Literature Review - Ginting, Selamat (Jurnal Penelitian Keperawatan Medik, 2023)
Diural Intermittent Fasting is a fasting activity that is believed to have various benefits such as having an effect on the pro-inflammatory substances interleukin and TNF. The aim of the research is to determine the effect of intermittent diural fasting on pro-inflammatory mediators using a literature review. The literature review was carried out by searching the electronic databases CINAHL, Proquest, Google Scholar, and Science Direct from 2012 to 2023. Key words used included Diural Intermittent Fasting, Proinflammatory. 122 articles were obtained, 44 articles were reviewed and only 6 articles met the criteria. Diural intermittent fasting has an effect on regulating blood sugar levels which will have an effect on inflammation.